Effect of formulation factors on in vitro transcorneal permeation of voriconazole from aqueous drops - Biswaranjan Mohanty; Sagar Kumar Mishra; Dipak K Majumdar (Wolters Kluwer Medknow Publications, 2013)
The purpose of this research was to evaluate the effect the formulation factors on in vitro permeation of voriconazole through freshly isolated goat and sheep corneas. An increase in the pH of the drops from 4.0 to 8.0 resulted in significant (P < 0.05) increase drug permeation. Raising concentration of the drops from 0.05% to 0.2% (w/v) significantly, (P < 0.05) increased drug permeation, but decreased the percent permeation. Corneal transport of voriconazole is both pH and concentration dependent. Eye drops containing disodium edetate (ethylenediaminetetraacetic acid) alone or combination with benzalkonium chloride showed significantly (P < 0.05) higher permeation as compared with control formulation. Addition of beta-cyclodextrin to the formulation enhanced corneal permeation of voriconazole. Compared with control formulation, voriconazole 0.2% (w/v) drop containing viscosity modifier produced significant (P < 0.05) decrease in permeation. Most of the formulations showed higher zone of inhibition against Candida albicans.